Sustainable International Parks in Egypt: Suggested Criteria for Design - LOBNA M. Moubarak; Aml Nour El-Dine; EZZAT ABDEL MONEIM MORGHANY (Journal of Urban Research, 2022)
Parks contributes to physical and mental well-being because they provide visitors with opportunities for recreation, education about nature, culture and social interactions. Parks also reduce pollution and effects of climate change in big cities and increase the local property values, and provide safe open spaces for social activities. Parks in developing countries face many challenges in terms of maintenance and availability of resources, especially international parks. To overcome these challenges, the concept of sustainability should be integrated in designing international parks to ensure the wise use of materials, energy, and water resources. This paper aims to suggest a group of criteria that can be used in designing and developing sustainable international parks. The proposed criteria have been classified into various categories related to energy, soil, water, materials and cultural diversity. The analytical methodology aimed to investigate a number of sustainable landscape systems in order to deduce criteria for sustainable international parks. The weights of the proposed criteria have been determined by using the inductive methodology though conducting a questionnaire directed to specialists in urban design, proposing a set list of design criteria for sustainable parks landscape design in developing countries.